2005
DOI: 10.1080/00288330.2005.9517334
|View full text |Cite
|
Sign up to set email alerts
|

Visual assessment of the reproductive condition of female western rock lobsters (Panulirus cygnus)

Abstract: An important issue when surveying the reproductive condition of large numbers of female Panulirus cygnus in the field is that each animal must be assessed quickly and accurately on the basis of only a few easily discernable criteria. The four biological criteria most commonly recorded for each lobster are: (1) ovigerous setae condition (not present, partially developed, and fully developed); (2) the presence (unused or eroded) of a spermatophore mass; (3) the presence and developmental stage of external ova; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…double) breeders. Recently, however, Melville-Smith and de Lestang (2005) showed that an ovary classified as ''developing'' in this situation is more likely a ''spent'' ovary containing residual atretic oocytes which make it appear yellow and developing, and so is only a single breeder. Furthermore, the DB 50 recorded by Chubb (1991) for Two Rocks, Dongara, and the Abrolhos Islands are the same as, or smaller than, the size at first maturity recorded by the same author for the same regions (Chubb, 1991), which casts doubt on the appropriateness of the criteria used to assign double breeding in this case.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…double) breeders. Recently, however, Melville-Smith and de Lestang (2005) showed that an ovary classified as ''developing'' in this situation is more likely a ''spent'' ovary containing residual atretic oocytes which make it appear yellow and developing, and so is only a single breeder. Furthermore, the DB 50 recorded by Chubb (1991) for Two Rocks, Dongara, and the Abrolhos Islands are the same as, or smaller than, the size at first maturity recorded by the same author for the same regions (Chubb, 1991), which casts doubt on the appropriateness of the criteria used to assign double breeding in this case.…”
Section: Discussionmentioning
confidence: 95%
“…It has not been possible to investigate whether DB 50 has decreased over the same period, because ovarian development has been recorded only since 1992. Moreover, establishing whether a female is a single or a double breeder is very sensitive to the time of year she is sampled (Melville-Smith and de Lestang, 2005), and suitable IBSS data are not available for this purpose in most years. However if, as we have suggested, DB 50 occurs on average two years after CL 50 , then it could be assumed that DB 50 has declined in a similar manner to CL 50 since the 1970s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Field studies of tropical palinurid lobsters have found that rapid and repetitive brood cycles are common, with up to 5 broods per annum (e.g., Juinio 1987;MacDiarmid 1989;Briones-Fourzán & Lozano-Álvarez 1992;Melville-Smith & de Lestang 2005;Senthil-Murugan et al 2005). Chittleborough (1976) reported that the sub-temperate species P. cygnus, when held in aquaria at a constant temperature of 25°C with abundant food, is capable of producing six broods a year.…”
Section: Discussionmentioning
confidence: 98%